2020
DOI: 10.1021/acs.joc.0c01035
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Controlled Chalcogenation and Chalcogenocyanation of Imidazopyridines in Water under Transition Metal-Free Conditions

Abstract: A sustainable and transition metal-free approach for C3 chalcogenation and chalcogenocyanation of imidazopyridines with KXCN (X = S or Se) has been developed under mild conditions. Importantly, this reaction was performed in the presence of catalytic iodine in aqueous medium, which afforded either chalcogenated or chalcogenocyanated imidazopyridines under temperature control. The current protocol featured a broad substrate scope, transition metal-free and organic solvent-free conditions, operational convenienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 86 publications
0
24
0
Order By: Relevance
“…In each centrosymmetric aggregate, the nitrogen donor to the diorganoselenium(II) centre is a nitrile-nitrogen atom with the transannular Se … Se separation within each dimer being 3.7828( 7) and 3.730( 14) Å, each value under the sum of the van der Waals radii for selenium (3.80 Å) [52]. In the crystals of 51 [94] and 52 [95] Se … N π-hole interactions are apparent with the ensuing two-molecule aggregates shown in Fig. 7g [5].…”
Section: Two-molecule Aggregates Featuring Two Se … N Interactions: Selenadiazole Ringsmentioning
confidence: 99%
“…In each centrosymmetric aggregate, the nitrogen donor to the diorganoselenium(II) centre is a nitrile-nitrogen atom with the transannular Se … Se separation within each dimer being 3.7828( 7) and 3.730( 14) Å, each value under the sum of the van der Waals radii for selenium (3.80 Å) [52]. In the crystals of 51 [94] and 52 [95] Se … N π-hole interactions are apparent with the ensuing two-molecule aggregates shown in Fig. 7g [5].…”
Section: Two-molecule Aggregates Featuring Two Se … N Interactions: Selenadiazole Ringsmentioning
confidence: 99%
“…Concurrently, Hao and Song along with their co-workers presented the molecular iodine-catalyzed direct C3-selective selenocyanation of 2-arylimidazo[1,2- a ]pyridines 11 with KSeCN in the most environmentally benign solvent, water, under ambient temperature. 28 The optimized condition for this C–H activation reaction is the use of 20 mol% of I 2 as catalyst and 1.5 equiv. of (diacetoxyiodo)benzene (PIDA) as an oxidant.…”
Section: Sodium/potassium Selenocyanate As Selenocyanating Agentsmentioning
confidence: 99%
“… 2 Hypervalent iodine reagents are considered as environmentally benign synthetic tools due to their readily available property and unique reactivities similar to those of heavy metals. 3 Previous studies have demonstrated that the direct functionalizations of C–H bonds via hypervalent iodine reagents are powerful tools for C–C and C–heteroatom bond formation, such as halogination, 4 hydroxylation, 5 alkoxylation, 6 acetoxylation, 7 amination, 8 azidation 9 thiocyanation, 10 etc.…”
Section: Introductionmentioning
confidence: 99%